Modeling the Frozen-In Anticyclone in the 2005 Arctic Summer Stratosphere - Allen, D. R.; Douglass, A. R.; Manney, G. L.; Strahan, S. E.; Krosschell, J. C.; Trueblood, J. V.; Nielsen, J. E.; Pawson, S.; Zhu, Z. (Atmospheric Chemistry and Physics, 2011)
Immediately following the breakup of the 2005 Arctic spring stratospheric vortex, a tropical air mass, characterized by low potential vorticity (PV) and high nitrous oxide (N2O), was advected poleward and became trapped in the easterly summer polar vortex. This feature, known as a "Frozen-In Anticyclone (FrIAC)", was observed in Earth Observing System (EOS) Aura Microwave Limb Sounder (MLS) data to span the potential temperature range from ~580 to 1100 K (~25 to 40 km altitude) and to persist from late March to late August 2005. This study compares MLS N2O observations with simulations from the Global Modeling Initiative (GMI) chemistry and transport model, the GEOS-5/MERRA Replay model, and the Van Leer Icosahedral Triangular Advection (VITA) isentropic transport model to elucidate the processes involved in the lifecycle of the FrIAC, which is here divided into three distinct phases. During the "spin-up phase" (March to early April), strong poleward flow resulted in a tight isolated anticyclonic vortex at ~70–90° N, marked with elevated N2O. GMI, Replay, and VITA all reliably simulated the spin-up of the FrIAC, although the GMI and Replay peak N2O values were too low. The FrIAC became trapped in the developing summer easterly flow and circulated around the polar region during the "anticyclonic phase" (early April to the end of May). During this phase, the FrIAC crossed directly over the pole between 7 and 14 April. The VITA and Replay simulations transported the N2O anomaly intact during this crossing, in agreement with MLS, but unrealistic dispersion of the anomaly occurred in the GMI simulation due to excessive numerical mixing of the polar cap. The vortex associated with the FrIAC was apparently resistant to the weak vertical shear during the anticyclonic phase, and it thereby protected the embedded N2O anomaly from stretching. The vortex decayed in late May due to diabatic processes, leaving the N2O anomaly exposed to horizontal and vertical wind shears during the "shearing phase" (June to August). The observed lifetime of the FrIAC during this phase is consistent with timescales calculated from the ambient horizontal and vertical wind shear. Replay maintained the horizontal structure of the N2O anomaly similar to MLS well into August. Isentropic simulations using VITA also captured the horizontal structure of the FrIAC during this phase, but small-scale structures maintained by VITA are problematic and show that important mixing processes are absent from this single-level simulation.